Narratives of Cancer Patients About Life Trajectories and Illness: Contributions of Sartrian existentialism to palliative care (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
How does a person perceive forced self-isolation in general and within him/herself? This article presents a qualitative analysis based on twelve interviews with people in palliative care. The study was based on the existentialist perspective and phenomenological method and concluded that people build strategies to face illness and death from their life trajectory, as they understand the realisation of their 'project of being'.
Keywords: Cancer; attitudes to death; palliative care; existentialism; phenomenological method; hospice